WTC COUGH SYNDROME: CURRENT PERSPECTIVES ON PATHOPHYSIOLOGY AND RESPIRATORY OUTCOMES AFTER THE SEPTEMBER 11 DISASTER (Web of Medicine: Journal of Medicine, Practice and Nursing, 2026)
The collapse of the World Trade Center (WTC) towers on September 11, 2001 (9/11), resulted in massive exposure to a complex mixture of pulverized building materials and combustion products, leading to a recognized occupational and environmental disease cluster (Prezant et al., 2002; Landrigan et al., 2004). This review focuses on the “WTC cough syndrome,” defined as a severe, persistent cough, often coupled with upper respiratory, lower respiratory, and gastroesophageal reflux disease (GERD) symptoms (Prezant et al., 2002). Longitudinal studies, particularly within the Fire Department of the City of New York (FDNY) cohort, have established a clear dose-response relationship between exposure intensity and disease incidence (Prezant et al., 2002; Wisnivesky et al., 2011). Pathophysiologically, the highly alkaline nature of the WTC dust induced chronic airway inflammation, leading to long-term sequelae such as accelerated decline in forced expiratory volume in 1 second (FEV1) and the emergence of obstructive airways disease (OAD) phenotypes, often characterized by restrictive patterns due to distal airway dysfunction (Aldrich et al., 2010; Berger et al., 2013). Persistent physical illness is highly comorbid with mental health disorders, notably Post-Traumatic Stress Disorder (PTSD) (Niles et al., 2011; Wisnivesky et al., 2011). Furthermore, WTC exposure is associated with increased risks of specific cancers, underscoring the necessity of ongoing, multidisciplinary longitudinal health surveillance.